Assessing the similarity of mental models of operating room team members and implications for patient safety: a prospective, replicated study. Issue 1 (December 2016) - Nakarada-Kordic, Ivana; Weller, Jennifer; Webster, Craig; Cumin, David; Frampton, Christopher; Boyd, Matt; Merry, Alan
Abstract Background Patient safety depends on effective teamwork. The similarity of team members' mental models - or their shared understanding–regarding clinical tasks is likely to influence the effectiveness of teamwork. Mental models have not been measured in the complex, high-acuity environment of the operating room (OR), where professionals of different backgrounds must work together to achieve the best surgical outcome for each patient. Therefore, we aimed to explore the similarity of mental models oftask sequence and ofresponsibility for task within multidisciplinary OR teams. Methods We developed a computer-based card sorting tool (Momento) to capture the information on mental models in 20 six-person surgical teams, each comprised of three subteams (anaesthesia, surgery, and nursing) for two simulated laparotomies. Team members sorted 20 cards depicting key tasks according to when in the procedure each task should be performed, and which subteam was primarily responsible for each task. Within each OR team and subteam, we conducted pairwise comparisons of scores to arrive at mean similarity scores for each task. Results Mean similarity score for task sequence was 87 % (range 57–97 %). Mean score for responsibility for task was 70 % (range = 38–100 %), but for half of the tasks was only 51 % (range = 38–69 %). Participants believed their own subteam was primarily responsible for approximately half the tasks in each procedure. Conclusions We found differences in the mental models of some OR team members about responsibility for and order of certain tasks in an emergency laparotomy. Momento is a tool that could help elucidate and better align the mental models of OR team members about surgical procedures and thereby improve teamwork and outcomes for patients.